Measurement of the $W \to \tau \nu_\tau$ cross section in $pp$ collisions at $\sqrt{s}=$7 TeV with the ATLAS experiment - ATLAS collaboration (3024 authors); Aguilar-Saavedra, Juan Antonio; Amaral, Pedro; Anjos, Nuno; Carvalho, Joao; Castro, Nuno Filipe; Conde Muino, Patricia; Do Valle Wemans, Andre; Fiolhais, Miguel; Gomes, Agostinho; Goncalo, Ricardo; Jorge, Pedro; et al. (My University, 2012)
The cross section for the production of W bosons with subsequent decay W to tau nu is measured with the ATLAS detector at the LHC. The analysis is based on a data sample that was recorded in 2010 at a proton-proton center-of-mass energy of sqrt(s) = 7 TeV and corresponds to an integrated luminosity of 34 pb^-1. The cross section is measured in a region of high detector acceptance and then extrapolated to the full phase space. The product of the total W production cross section and the W to tau nu branching ratio is measured to be 11.1 +/- 0.3 (stat) +/- 1.7 (syst) +/- 0.4 (lumi) nb.